2009
DOI: 10.1590/s1519-69842009000500023
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspects of sharks caught off the Coast of Pernambuco, Northeast Brazil

Abstract: One hundred seventeen specimens of sharks were caught along the coast of Pernambuco State, Northern Brazil, between May 2004 and May 2007, among which 86 were blacknose sharks, Carcharhinus acronotus, enabling a more detailed study of the species. Blacknose sharks were caught in the 2 study areas along the Boa Viagem/Piedade and Paiva beaches, accounting for the highest relative abundance among the species caught (73.5% of total). Potentially dangerous sharks, tiger and bull sharks, were also caught in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The tiger shark is a relatively rare species (Fischer et al 2009;Harry et al 2011;Afonso et al 2012b;Coelho et al 2012;Holmes et al 2012) probably due to its top predator position in the food chain, which leads to their populations being generally comprised of a small number of individuals (Ebert et al 2013;Sulikowski et al 2016). As in the current study, age and growth assessments of G. cuvier are usually based on a small amount of samples, mostly below 50 (De Crosta et al 1984;Branstetter et al 1987).…”
Section: Discussionmentioning
confidence: 74%
“…The tiger shark is a relatively rare species (Fischer et al 2009;Harry et al 2011;Afonso et al 2012b;Coelho et al 2012;Holmes et al 2012) probably due to its top predator position in the food chain, which leads to their populations being generally comprised of a small number of individuals (Ebert et al 2013;Sulikowski et al 2016). As in the current study, age and growth assessments of G. cuvier are usually based on a small amount of samples, mostly below 50 (De Crosta et al 1984;Branstetter et al 1987).…”
Section: Discussionmentioning
confidence: 74%
“…A região metropolitana do Recife (RMR) possui uma linha de costa com aproximadamente 60 km, que engloba as praias do Paiva, Candeias, Piedade, Boa Viagem e Pina, entre outras, com temperatura da água variando entre 24 e 30ºC, durante o verão (FISCHER et al, 2009). A praia do Paiva (Erro!…”
Section: áRea De Estudounclassified
“…Since 1992, the metropolitan region of Recife, Brazil, exhibits one the highest shark attack rates per unit of area in the world, accounting for 53 attacks which resulted in 20 fatalities. Relative abundances assessed off Recife (Fischer et al 2009), together with forensic analysis (Gadig andSazima 2003, Hazin et al 2008) indicated the tiger shark, Galeocerdo cuvier, and the bull shark, Carcharhinus leucas, to be responsible for most of the attacks. Both species are considered potentially aggressive and have been frequently implicated in attacks on humans worldwide (International Shark Attack File, http:// www.flmnh.ufl.edu/fish/Sharks/ISAF/ISAF.htm.…”
Section: Introductionmentioning
confidence: 99%